Estimation of the Effect of Phospholipase Extracted from Candida Albicans on Human Lymphocytes Using MTT Assay (In Vitro Study) - Jasim, Saif Talib (American Journal of Biology and Natural Sciences, 2025)
Background & aim: One of the common fungal illnesses brought on by the genus Candida is candidiasis. Clinical manifestations include everything from mucocutaneous colonization to deadly infections like candidemia that spread widely. So, the current investigation was aimed to estimate of the effect of phospholipase (PL) extracted from Candida albicans on human lymphocytes using MTT assay (in vitro study). Materials & methods: Between September 2024 and April 2025, 180 married patients with VVC symptoms had their vaginal swabs taken at Al-Yarmok Hospital in Baghdad, Iraq. The age range of the patients ranged from 20 to 60 years. After being combined with 10% KOH, the initial batch of vaginal swab samples was inspected under a microscope to check for the presence of Candida. Sabouraud Dextrose agar (SDA) was used to hold the second round of vaginal swab samples. The phospholipase production of the isolates was assayed using the egg yolk agar plate. The effect of the enzyme on lymphocytes was tested using MTT assay. Results: Using a 10% KOH solution, 180 samples were directly inspected under a microscope; of these, 51(28.3%) were found to be positive and 129(71.7%) to be negative. The results showed that after 24 hours of incubation, lymphocyte inhibitory rate was 9.7% at 5µL of PL, while at 10µL of PL, lymphocyte inhibitory rate was 13.2%, and at 15µL of PL, lymphocyte inhibitory rate was 16.0%. After 48 hours of incubation, it was found that at 5µL of phospholipase, lymphocyte inhibitory rate was 14.60%, while at 10µL of PL, inhibitory rate inhibition was 24.70%, and at 15µL of PL, inhibitory rate inhibition was 37.40%. After 72 hours of incubation, it was found that at 5 µl of PL, the inhibitory rate of lymphocytes was 38.1%, while at 10 µl of PL, the inhibitory rate of lymphocytes was 59.2%, and at 15 µl of PL, inhibitory rate of lymphocytes was 76.34%. Conclusion: it is concluded that the phospholipase enzyme is considered one of the most important causes that increase the risk of infection with vulvovaginal candidiasis (VVC).